Influence of contextual variables on styles of play in soccer - Fernandez-Navarro, J.; Fradua, L.; Zubillaga, A.; McRobert, A. P. (International Journal of Performance Analysis in Sport, 2018)
The aim of the present study was to evaluate the effect of match status, venue, and quality of opposition on the styles of play in soccer. Data were collected from 380 games of the English Premier League from the 2015-2016 season. Linear mixed models were applied to evaluate the influence of these contextual variables on membership scores for Direct Play, Counterattack, Maintenance, Build Up, Sustained Threat, Fast Tempo, Crossing, and High Pressure. The results showed that match status had a significant effect on the eight styles of play (all P < 0.001), venue had a significant effect on all styles of play (P < 0.01) except Counterattack and Maintenance, and quality of opposition had a significant effect on all styles of play (P < 0.05) except Counterattack. Moreover, the interaction between match status and quality of opposition, and venue and quality of opposition showed significant effects on some styles of play. The results of this study imply that contextual variables influence the use of styles of play in soccer match play. Consequently, this provides meaningful recommendations for practitioners in soccer.